2022
DOI: 10.3389/fneur.2022.884693
|View full text |Cite
|
Sign up to set email alerts
|

Interpretable Machine Learning Modeling for Ischemic Stroke Outcome Prediction

Abstract: Background and PurposeMechanical thrombectomy greatly improves stroke outcomes. Nonetheless, some patients fall short of full recovery despite good reperfusion. The purpose of this study was to develop machine learning (ML) models for the pre-interventional prediction of functional outcome at 3 months of thrombectomy in acute ischemic stroke (AIS), using clinical and auto-extractable radiological information consistently available upon first emergency evaluation.Materials and MethodsA two-center retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…Similarly, automated atrophy quantification strongly predicts mRS, with an odds ratio of 0.65 per 5% increase in intracranial cerebrospinal fluid volume ( 15 ). A previous machine learning study of NCCT and CTA features using e-Stroke found that age, baseline NIHSS, occlusion side, atrophy and e-ASPECTS were the best predictors for mRS at 90 days, in keeping with the results shown here ( 16 ). The clinical variables used in this study—age and presenting NIHSS—have previously been used as a prognostic score, which was also an independent predictor of outcome in EVT ( 17 ).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, automated atrophy quantification strongly predicts mRS, with an odds ratio of 0.65 per 5% increase in intracranial cerebrospinal fluid volume ( 15 ). A previous machine learning study of NCCT and CTA features using e-Stroke found that age, baseline NIHSS, occlusion side, atrophy and e-ASPECTS were the best predictors for mRS at 90 days, in keeping with the results shown here ( 16 ). The clinical variables used in this study—age and presenting NIHSS—have previously been used as a prognostic score, which was also an independent predictor of outcome in EVT ( 17 ).…”
Section: Discussionsupporting
confidence: 90%
“…Machine learning (ML) has emerged as a promising predictive tool in medicine and has been applied in many medical fields, such as ischemic stroke outcome prediction [ 19 , 20 , 21 , 22 ], biomedical research [ 23 ] and rehabilitation for chronic stroke survivors [ 24 ], and so on. Because in the process of modeling, machine learning can fit the complex relationship in multi-dimensional data, extract subtle information, and automatically summarize and generalize to obtain new knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning has been limited in the medical field due to its black-box nature [ 25 , 26 ]. However, the latest machine learning models have been made interpretable by Shapley Additive Explanations (SHAP), which prompts the application of ML to be further developed [ 19 , 20 ]. The SHAP is a novel, cutting-edge machine learning algorithm which can visualize the relationship between each feature and the related predictive ability and can more intuitively understand the importance of features and enhance clinical interpretability.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, machine learning (ML) has gradually been widely used in the medical field, and several prognostic and diagnostic models have been developed for ischemic stroke patients. 12,13 Optimization of models by fitting machine learning to big data has shown good predictive performance. Such ML based modeling solutions can help clinicians to better individualize their treatments.…”
Section: Text Introductionmentioning
confidence: 99%